Tariff rate quotas and the economic impacts of agricultural trade liberalization in the WTO - Herrmann, Roland; Kramb, Marc Christopher; Mönnich, Christina; Justus Liebig University Giessen (My University, 2000)
Since their implementation at the Uruguay Round, tariff rate quotas (TRQs) have become a widely used instrument of trade policy in agricultural trade. With almost 1300 TRQs scheduled at the WTO, it seems worthwhile to examine their economic effects more closely. This is what this paper does. First, the theoretical background of TRQs is examined. Then a short overview of the Uruguay Round as their institutional background is given. We demonstrate that official statistics, which do not count TRQs as non-tariff barriers, are at least highly misleading. Very often, their effects are the same as those of regular quotas, including redistributive effects. The prominent example of the European Banana regime is used to illustrate all of these points.
Keywords: Agrarhandel; World Trade Organization; Agriculture in International Trade; Commercial Policy; Protection; Promotion; Trade Negotiations; ddc:650